2012
DOI: 10.3329/dujps.v11i1.12484
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of Floating Alginate Beads of Diclofenac Sodium

Abstract: ABSTRACT:The objective of this present investigation is to develop gastroretentive sustained release alginate beads of Diclofenac sodium by the ionotropic gelation method. The floating beads were prepared by dispersing Diclofenac sodium together with CaCO 3 (as gas forming agent) into a solution of sodium alginate. The resulting solution was then extruded through a 22 gauge syringe needle into 100 ml cross-linking solution containing calcium chloride (1% w/v) plus acetic acid (10% v/v). Prepared beads were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 13 publications
3
15
0
Order By: Relevance
“…1). This was in a good correlation with Rasel and Hasan, who found that the release of diclofenac sodium significantly decreased from 76.7% to 69.1%, as the amount of SA increased from 2 g to 4 g [15]. This could be ascribed to the formation of a tight junction between the glucuronic acid residues as a result of cross-linking.…”
Section: In Vitro Release Studysupporting
confidence: 75%
See 3 more Smart Citations
“…1). This was in a good correlation with Rasel and Hasan, who found that the release of diclofenac sodium significantly decreased from 76.7% to 69.1%, as the amount of SA increased from 2 g to 4 g [15]. This could be ascribed to the formation of a tight junction between the glucuronic acid residues as a result of cross-linking.…”
Section: In Vitro Release Studysupporting
confidence: 75%
“…2). An increase in the cross-linking agent concentration, led to the formation of more rigid gel structure with smaller pore size, which retained the drug and retarded the penetration of the dissolution medium into the beads which in turn decreased the total amount of the drug released [15]. This was in a good correlation with Mandal et al who reported a significant decrease in the amount of trimetazidine dihydrochloride release from 38% to 30% with an increase in Cacl2 concentration from 1% to 3% [41].…”
Section: In Vitro Release Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The rough and approximately porous surface characteristics of alginate beads shown in SEM pictures is in good agreement with the other studies which can be explained by the egg-box structure of calcium alginate beads. [21][22][23][24] Alginate is able to form gel by reaction with divalent cations such as Ca 2+ . Gelation of alginate is mainly achieved by the exchange of Na + from the guluronic acids with Ca 2+ , and stacking of these guluronic groups to form the characteristic egg-box structure.…”
Section: Discussionmentioning
confidence: 99%